Аналіз впливу обважнених подач на розподіл матеріалів і газів в доменних печах - Крячко, Г.Ю.; Сігарьов, Є.М. (Physico-technological Institute of Metals and Alloys, 2025)
The paper presents the results of the analysis and generalization of data on the redistribution of gas flows between the center and periphery of blast furnaces equipped with conical charging devices when using weighted feeds. It was found that the use of weighted feeds causes a redistribution of the gas flow in the opposite direction from the optimized relatively longterm operating mode, with unloading of the periphery, the bottom of which is a generator of hot reducing gases, and loading of the center of the furnace with an iron ore component. It was found that the excessive force action of the weighted iron ore part of the feed on the charge column during its loading, as well as the overlap of the axial vent with an iron ore layer, which together lead to an increase in the resistance of the charge column, prevent the achievement of the expected reduction in the pressure drop in the charge column, the possibility of adding blast and increasing the furnace productivity. It has been confirmed that the 4K4A separate charging system loses its technological purpose when using conical charging devices, which significantly limits the control of the furnace from above, therefore the recommendation to spread the experience of using these feeds is not weighted. Weighted separate feeds according to the 4K4A system are suitable only for temporary  uppression of excessive central gas flow. A classification of the causes of the negative impact of weighted feeds when using cone-type charging devices is proposed. It is recommended to avoid charging systems containing 3-4 skip feeds of iron ore materials in favor of 3 skip feeds of coke when choosing the feed mass for furnaces equipped with cone distributors and in conditions of pulverized coal fuel injection. A cardinal solution to eliminate obstacles to the use of weighted feeds is to replace cone-type charging devices with cone-less tray-type ones.